2013
DOI: 10.1111/bjd.12474
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in the treatment of pemphigus vulgaris: experience in 23 patients

Abstract: Methotrexate is a useful and well-tolerated therapy with considerable steroid-sparing effect in patients with pemphigus vulgaris. It may be considered a first-line adjuvant therapy in the treatment of this difficult disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
2
29
0
5
Order By: Relevance
“…Although G6PD is X-linked, women who are heterozygous for G6PD mutations can demonstrate wide phenotypic variability owing to random X-inactivation in erythrocytes 228 . Methotrexate (a chemotherapeutic drug) is another steroid-sparing agent, although only small case series support its efficacy in pemphigus 229 . Small case series support the efficacy of cyclosporine (a T cell inhibitor) in pemphigus 230,231 , although larger clinical trials have suggested inferior to no benefit and a higher number of adverse effects in the treatment group 232,233 .…”
Section: Managementmentioning
confidence: 99%
“…Although G6PD is X-linked, women who are heterozygous for G6PD mutations can demonstrate wide phenotypic variability owing to random X-inactivation in erythrocytes 228 . Methotrexate (a chemotherapeutic drug) is another steroid-sparing agent, although only small case series support its efficacy in pemphigus 229 . Small case series support the efficacy of cyclosporine (a T cell inhibitor) in pemphigus 230,231 , although larger clinical trials have suggested inferior to no benefit and a higher number of adverse effects in the treatment group 232,233 .…”
Section: Managementmentioning
confidence: 99%
“…A retrospective review by Tran et al . on the adjunctive use of methotrexate in patients with PV has demonstrated its effectiveness as a corticosteroid‐sparing agent; 23 patients with PV were treated with methotrexate, of whom 21 (91%) experienced improvement (as measured by reduction in the prednisolone dose).…”
Section: Adjuvant Drugsmentioning
confidence: 99%
“…Für die Immunsuppressiva Azathioprin, Mycophenolat-Mofetil, Mycophenolsäure, Methotrexat und Cyclophosphamid konnten klinische Studien einen steroideinsparenden Effekt in der adjuvanten Gabe mit systemischen Kortikosteroiden beim Pemphigus vulgaris/foliaceus aufweisen [3][4][5][6][7][8][9][10][11].…”
unclassified